The Influence of Pricing, Cancellation Policy, Location and Facilities on The Performance of 3-Star Hotels in Indonesia - Wahyu Fadli Satrya; Laura Lahindah (Eduvest - Journal of Universal Studies, 2025)
This study aims to show the factors that influence the performance of 3-star hotels in Indonesia. This study uses a quantitative approach to analyze the influence of pricing, cancellation policies, location, and facilities on hotel performance. Data are generated from booking.com, which is the largest online travel application in the world. In addition, interviews with informants were also conducted to enrich the discussion of this study. Statistical analysis was carried out using Structural Equation Modeling (SEM) using SmartPLS. The results of the statistical analysis show that price and facilities have a significant influence on the performance of 3-star hotels in Indonesia, with t-values of 6,387 and 5,679 (p-value <0.05). On the other hand, cancellation policies and location do not show a significant influence on hotel performance with t values of 1,655 and 1,348 (p-value> 0.05).